A second species of Oristicta Tillyard (Odonata: Isostictidae) - Theischinger, Günther; Burwell, Chris J. (Zootaxa, 2017)
In order to include an additional species in the genus Oristicta Tillyard, 1913, the lectotype of its sole species Oristicta filicicola Tillyard, 1913 and the holotype of Phasmosticta interposita Lieftinck, 1951, its assumed junior synonym, the original descriptions of both and numerous museum specimens identified as O. filicicola are studied and discussed. In spite of some variability being noted, it is concluded that they all are O. filicicola which is considered a monotypic species. The additional species is described as Oristicta rosendaleorum sp. nov. It is comprehensively illustrated, and its affinities are discussed. Possibly sympatric in places with O. filicicola, Oristicta rosendaleorum sp. nov. has richer black markings, lacks posterolateral processes/horns on the male’s pronotum (present in O. filicicola), and the male anal appendages are of different form. Oristicta filicicola is known from far north-eastern Queensland from Hammond Island (10.5°S) at the tip of Cape York to the Paluma Range (19°S) in the southern Wet Tropics Bioregion. Oristicta rosendaleorum sp. nov. is currently known from only two localities within 20 km of Lakeland (15.9°S) in south-eastern Cape York Peninsula.